Evaluation of an application for making palmtop computers accessible to individuals with intellectual disabilities. - Stock SE; Davies DK; Davies KR; Wehmeyer ML (Journal of Intellectual & Developmental Disability, 2006)
Background Palmtop computers provide a promising mobile platform to address barriers to computer-based supports for people with intellectual disabilities. This study evaluated a specially designed interface to make navigation and features of palmtop computers more accessible to users with intellectual disabilities.Method The specialised cognitively accessible interface was compared with a standard Windows CE interface. Participants completed a structured set of navigation/computer use tasks using both the experimental and control conditions. Measurements included the amount of assistance needed and errors made in completing the navigation/computer use tasks.Results Participants (N = 32) made significantly fewer errors (p<.001) and required significantly fewer prompts (p<.001) while using the specialised software interface compared to the mainstream Windows interface.Conclusions The research demonstrates the feasibility of using special software design methods, such as linear program flows, error minimisation and the incorporation of repetition and consistency, to improve access to palmtop computers for individuals with intellectual disabilities. Issues related to designing cognitively accessible interfaces are discussed.